Bilateral Lumbar Facet Synovial Cysts as a Cause of Radiculopathy - Pawin Kasempipatchai; Verapan Kuansongtham; Monchai Ruangchainikom; Khin Myat Myat Lwin (Case Reports in Orthopedics)
Remarkable advancements in endoscopic spinal surgery have led to successful outcomes comparable to those of conventional open surgery with the benefits of less traumatization and postoperative spinal instability. Bilateral lumbar facet cysts are rarely found in the spinal canal. We report a rare case of L4–L5 bilateral lumbar facet cysts compressing the nerve root in a patient who presented with L5 radiculopathy. Endoscopic decompression and removal of the cysts without fusion were performed. Histopathology revealed synovial cysts. Postoperatively, the patient showed a total resolution of symptoms with sustained benefits at the final evaluation. No recurrence of pain and no further segmental instability were observed at the 1-year follow-up.